2021
DOI: 10.3389/fpsyt.2021.653482
|View full text |Cite|
|
Sign up to set email alerts
|

Improvements on Clinical Status of Adolescents With Anorexia Nervosa in Inpatient and Day Hospital Treatment: A Retrospective Pilot Study

Abstract: Introduction: Medical and psychiatric complications and treatment compliance are important considerations in determining the treatment program for patients with severe anorexia nervosa (AN). Clinical practice guidelines agree that an outpatient program is the first choice for the treatment of most eating disorders, but vary in supporting these programs for AN. However, inpatient care is known to be costly and the risk of relapse and readmission is high. This pilot study aimed to describe the first data on an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Despite difficulties in managing patients’ ED behaviours outside of treatment and the necessity of patient motivation, DP treatment appears to permit greater links to one’s home environment, greater responsibility in recovery, and a smoother transition out of intensive treatment. These findings provide support for DP treatment as an alternative to IP treatment for individuals with severe AN [ 10 , 26 ] and calls for the introduction of more evidence-based intensive DP treatment programs to meet the needs of all patients with AN [ 27 ]. Further research comparing the two intensive treatment approaches is necessary, as while both settings are valued, it remains unknown which treatments work best for whom at what time.…”
Section: Discussionmentioning
confidence: 85%
“…Despite difficulties in managing patients’ ED behaviours outside of treatment and the necessity of patient motivation, DP treatment appears to permit greater links to one’s home environment, greater responsibility in recovery, and a smoother transition out of intensive treatment. These findings provide support for DP treatment as an alternative to IP treatment for individuals with severe AN [ 10 , 26 ] and calls for the introduction of more evidence-based intensive DP treatment programs to meet the needs of all patients with AN [ 27 ]. Further research comparing the two intensive treatment approaches is necessary, as while both settings are valued, it remains unknown which treatments work best for whom at what time.…”
Section: Discussionmentioning
confidence: 85%
“…Of the six studies that utilized the CDI, four reported significant reductions in depressive symptoms at discharge (Girz et al, 2013;Henderson et al, 2014;Ornstein et al, 2012;Rienecke & Richmond, 2018). Similarly, the improvements in anxiety and general functioning were observed in studies utilizing the MRAOS, RCMAS and MASC at discharge (Henderson et al, 2014;Ornstein et al, 2012;Zanna et al, 2021). Regarding follow-up data, Girz et al (2013) found significant reductions in depressive and anxiety symptoms at three-and six-month follow-up utilizing the CDI and MASC respectively.…”
Section: Other Psychological Measuresmentioning
confidence: 83%
“…Four studies did not conduct inferential statistical analyses to assess changes in weight (Girz et al, 2013;Grewal et al, 2014;Lazaro et al, 2011;Ngo & Isserlin, 2014), with several studies not reporting on effect sizes. Of the studies that reported effect sizes related to changes in body weight post-treatment, two studies reported small effect (d = 0.30 to 0.50; Goldstein et al, 2011; r = 0.10 to 0.30; Bryson et al, 2018) and two studies reported medium to large effect sizes (d = 0.50 and higher; Simic et al, 2018;r = 0.30 and higher;Bryson et al, 2018;Zanna et al, 2021). Goldstein et al (2011) reported medium to large effect sizes in six-month followup (d = 0.86).…”
Section: Parental Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…), in agreement with previous reports [ 26 ]. Recent research comparing inpatient treatment with outpatient treatment has described the advantages of this outpatient management approach; the rapid return to normal social activities and family environment favours a better treatment process, both for weight restoration and psychological recovery [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%